The Wireless Library: Technical and Organizational Aspects - Schneider, Gerhard (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
The deployment of (wireless) networks in a library in order to help users to access modern digital data is possible at low cost. All necessary hardware and software components are readily available. The technical as well as organisatorial issues can be solved in a satisfactory way requiring little or no additional work for librarians. It is even possible to charge users for outside connections. Management has to decide whether this is a good idea.